Rooted in crisis, growing solutions: economic impacts and adaptive pathways for Fiji’s climate-threatened sugarcane industry - Khan, Shifadjzic; Yun, Byung-Wook (Frontiers in Climate, 2025)
Small Island Developing States (SIDS) face accelerating climate hazards that undermine agricultural productivity. Fiji’s sugarcane sector, which is central to rural incomes and foreign exchange earnings, is increasingly affected by floods, droughts, cyclones, irregular rainfall, and rising input costs. Assessing farm-level climate vulnerability is essential for guiding effective adaptation. A convergent mixed-methods design was applied, integrating surveys from 100 smallholder farmers, panel regression to estimate hazard-specific yield elasticities, and AI-assisted scenario modeling aligned with Asian Development Bank climate projections. Stratified sampling captured variation in farm size, location, and cooperative membership, and survey responses were cross-validated with production records to ensure reliability. Flood-related hazards showed the strongest negative association with multi-year yields (β = −0.49, p < 0.001), followed by irregular rainfall and drought effects. Flood impacts were most severe because water-logging, access disruption, and delayed harvesting weakened ratoons and reduced subsequent cycle yields. Socio-institutional constraints, including limited cooperative support, inadequate extension services, and low youth engagement, intensified vulnerability. Grassroots participation, modeled on South Korea’s Saemaul Undong, can strengthen local coordination and adoption of adaptive practices. AI-assisted scenarios provided validated projections and identified priority adaptation pathways. The findings indicate a hydrology-first risk profile in Fiji’s coastal sugarcane systems. Targeted water management and accelerated varietal upgrading are essential to sustaining productivity under increasing climatic extremes. Coordinated investments in drainage, stress-tolerant cultivars, and farmer–extension partnerships can narrow adaptation gaps and stabilize rural livelihoods. Although focused on Fiji, the analysis provides a transferable framework for estimating climate-induced yield elasticities and validating adaptation strategies in coastal smallholder cane systems across tropical Asia, Africa, and the Caribbean. The integrated empirical and AI-based methodology offers a replicable template for climate resilience assessment in tropical agriculture.